2020
DOI: 10.1093/hmg/ddaa047
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics hallmarks OPA1 variants correlating with their in vitro phenotype and predicting clinical severity

Abstract: Interpretation of variants of uncertain significance is an actual major challenge. We addressed this question on a set of OPA1 missense variants responsible for variable severity of neurological impairments. We used targeted metabolomics to explore the different signatures of OPA1 variants expressed in Opa1 deleted mouse embryonic fibroblasts (Opa1−/− MEFs), grown under selective conditions. Multivariate analyses of data discriminated Opa1+/+ from Opa1−/− MEFs metabolic signatures and classified OPA1 variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
5
12
1
Order By: Relevance
“…It is of interest that the substantial slowdown of autophagy in these cells is in line with the results of our metabolomics analysis evidencing also a significant fall in the cellular amino acids content, more severe in the R445H than in D603H MEFs ( 71 ). As stated above, ORMs 0, 2 and 14 were able to enhance the ATP content and, although ORM0 less efficiently, to induce the LC3-I cleavage in R445H MEFs, indicating re-activation of the autophagic process.…”
Section: Discussionsupporting
confidence: 84%
“…It is of interest that the substantial slowdown of autophagy in these cells is in line with the results of our metabolomics analysis evidencing also a significant fall in the cellular amino acids content, more severe in the R445H than in D603H MEFs ( 71 ). As stated above, ORMs 0, 2 and 14 were able to enhance the ATP content and, although ORM0 less efficiently, to induce the LC3-I cleavage in R445H MEFs, indicating re-activation of the autophagic process.…”
Section: Discussionsupporting
confidence: 84%
“…However, we have previously shown a sharp drop in the concentration of taurine in the aqueous humor of patients with glaucoma where taurine is considered to play an osmolytic role ( 39 ). We also previously found a drop in taurine concentration in mouse embryonic fibroblasts in which OPA1 gene has been inactivated and have found that the severity of the OPA1 was tightly correlated to the taurine level in these cells ( 40 ). Taurine is present in high concentration in oxidative tissues, where it plays a role in stabilizing the inner mitochondrial membrane gradient and the equilibrium between NAD/NADH and GSH/GSSG (oxidized and reduced forms of glutathione) ( 41 ).…”
Section: Discussionmentioning
confidence: 67%
“…Alterations of purine metabolism (xanthine, hypoxanthine, and inosine), lipid metabolism (1-oleyl-rac-glycerol, rac-glycerol-1-myristate and glycerate, phosphocholine, and choline), and of few aminoacids (cystine, aspartate, glutamic acid, and urocanate) have been described in plasma from patients carrying OPA1 mutations [ 98 ]. Concordantly, variations in several phospholipids concentration have been reported in mouse embryonic fibroblasts (MEF) Opa1 -/- [ 99 ], MEF Opa1 -/- expressing different OPA1 mutants [ 100 ], and in the Opa1 delTTAG/+ mouse model, specifically in the optic nerve and in plasma [ 101 ]. Thus, while alterations in purine metabolism and reduced glutamic acid are recurrent in mitochondrial diseases or in the presence of ATP depletion [ 102 , 103 , 104 , 105 ], changes in phospholipids, confirmed in three different models, may be the effect of mitochondrial membrane remodeling due to OPA1 dysfunction, in particular the defective mitochondrial fusion.…”
Section: Mitochondrial Dynamics Failure: From Dominant Optic Atrophy mentioning
confidence: 90%